RENACARDIAL SYNDROME IN DIABETIC NEPHROPATHY - Sapaeva Z.A; Djumaniyazova Z.F (Scholar Express Journals, 2021)
This article presents data on the prevalence of different variants of heart remodeling in patients with type 2 diabetes with DN. It was revealed that the severity of structural and functional changes in the heart depends on the stage of diabetic nephropathy. New data are presented that establish a clear relationship between indicators characterizing the structural and functional state of the heart and kidneys in patients with type 2 diabetes with DN. New facts have been obtained indicating that the combined renocardial disorders in patients with type 2 diabetes are based on impaired vascular endothelial function.
Keywords: Diabetes mellitus; diabetic nephropathy; microalbuminuria; glomerular filtration rate